Mathematical modelling of combined process drying by using bond graph approach. (2015) - Oueslati, Hatem; Mabrouk, Salah Ben; Mami, Abdelkader
The main objective of this work is to quantify the energetic interest of combined drying process of natural products. This method of drying is realised in a climatic wind tunnel, seat of a flow of hot air and in the presence of a radiation source. A mathematical model that describes the phenomena of heat and mass transfers during the drying of a wet agricultural product has been determined by the use of the pseudo-bond graph methodology. Such methodology was very appropriate for this industrial process since it allows good management of the non-linearity present in the system. Some drying tests were realised on tomatoes and experimental results are compared with theoretical results for validation of the developed model.